1984
DOI: 10.1002/jcu.1870120703
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Assessment of Fetal Growth in the Nonhuman Primate (Macaca mulatta)

Abstract: Serial ultrasound measurements of fetal growth were made during uncomplicated pregnancy in 28 time-mated rhesus monkeys. Gestational sac (GS) size, crown-rump length (CRL), biparietal diameter (BPD), head circumference (HC), head area (HA), abdominal circumference (AC), abdominal area (AA), and femur length (FL) were measured. Average longitudinal growth curves for each parameter were obtained from individual fetal growth curves. Data analysis indicated that the linear model was optimal for GS, CRL, HA, AA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…RhCMV DNA PCR evaluation of placental tissues and fetal tissues confirmed a protective role of maternal pre-existing immunity in preventing the spread and replication of RhCMV in vivo during first trimester infection of rhesus macaques (S2 Table ). The fetal growth parameters in the CD4+ T lymphocyte-depleted RhCMV reinfected dams were comparable to the RhCMV-seropositive control dams (S5 Fig) and within the normal range of reference values established in rhesus macaques [37].…”
Section: Plos Pathogenssupporting
confidence: 74%
See 2 more Smart Citations
“…RhCMV DNA PCR evaluation of placental tissues and fetal tissues confirmed a protective role of maternal pre-existing immunity in preventing the spread and replication of RhCMV in vivo during first trimester infection of rhesus macaques (S2 Table ). The fetal growth parameters in the CD4+ T lymphocyte-depleted RhCMV reinfected dams were comparable to the RhCMV-seropositive control dams (S5 Fig) and within the normal range of reference values established in rhesus macaques [37].…”
Section: Plos Pathogenssupporting
confidence: 74%
“… (A) BPD of CMV-seropositive reinfected (green) and CMV-seropositive controls (grey) fetuses compared to reference values [ 37 ]. (B) FL of CMV-seropositive reinfected (green) and CMV-seropositive control (grey) fetuses compared to reference values [ 37 ]. …”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…We faced the challenge of having no a priori knowledge of conception dates for females in the VRC colony. Ultrasound was used to estimate the gestational age of the fetus based on fetal head circumference [47] . Additional dates were scheduled in April and July 2012 for blood draws, physical exams, and ultrasounds to confirm healthy gestation.…”
Section: Methodsmentioning
confidence: 99%
“…Trans-abdominal ultrasonography is another tool utilized with growing frequency within wildlife research and captive wildlife management for health, reproductive assessment, and pregnancy diagnosis [Hildebrandt et al, 2003;G€ oritz et al, 2004]. The usefulness of ultrasonography in pregnancy diagnosis and monitoring has been demonstrated in other non-human primates [Nyland et al, 1984;Tarantal and Hendrickx, 1988a,b], but, to our knowledge, has not been reported in the potto.…”
Section: Introductionmentioning
confidence: 99%